The Digital Investors: How Financial Literacy, Investment Savvy, and App Simplicity Fuel Gen Z’s Stock Market Frenzy - Anastasia Septianingtias Virgo Gare; Nanang Shonhadji (Center for Indonesian Accounting Studies, 2026)
Research Objective – This study specifically aims to analyze the influence of financial literacy, investment knowledge, and application ease on the interest of Generation Z in Surabaya regarding online stock investing. Furthermore, this research intends to evaluate the extent to which these cognitive and technological factors shape investment intentions among students navigating the dynamics of the digital capital market. Research Method - This research employs a quantitative approach using primary data collected through questionnaires distributed to 75 respondents representing the Generation Z population. The data analysis technique applied is Structural Equation Modeling with a Partial Least Squares (SEM-PLS) approach using SmartPLS software to test validity, reliability, and the relationships between research variables. The analysis process was carried out systematically to ensure the accuracy of the hypothesis testing results. Research Findings - The research results reveal that financial literacy has a positive and significant effect on investment interest, indicating that an understanding of risk management is the primary foundation for Generation Z to begin investing. However, unique findings emerged where investment knowledge and ease of application were found to have no significant effect on their investment interest. This indicates that the availability of sophisticated technological features and theoretical knowledge alone are not strong enough to trigger investment actions if not accompanied by proficient financial literacy and actual financial readiness. Theoretical and Policy Implications – These findings imply that future capital market education should emphasize risk management and financial management practices rather than merely introducing application features. Digital literacy policies need to be directed toward increasing the confidence of young potential investors in making responsible and sustainable investment decisions. Research Novelty - The novelty of this research lies in uncovering the fact that for digital natives, technological ease is considered a minimum standard facility rather than a primary driver in online stock investment decision-making.